2018
DOI: 10.1007/s11356-018-2500-6
|View full text |Cite
|
Sign up to set email alerts
|

Mg–Fe layered double hydroxide assembled on biochar derived from rice husk ash: facile synthesis and application in efficient removal of heavy metals

Abstract: The pollution of toxic and persistent heavy metals commonly exist in water environment; such multi-component pollutants pose a serious threat to human beings and other organisms. Herein, to make full use of the advantages of both layered double hydroxide (LDH) and rice husk ash (RHA), a novel Mg-Fe-LDH-RHA functional material was synthesized by assembling LDH on the biochar derived from RHA and used as an adsorbent for removal of heavy metal ions including Pb, Cu, Co, Ni, Zn, and Cd. The adsorption kinetics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…Absorption sites have also increased. Silica aerogel, N-doped carbon nanosheet, graphene, biochar, and other materials that can provide many absorption sites and stable attachment sites can be used as substrates [90][91][92][93][94][95]. Because carbon-based materials contain more functional groups and larger specific surface areas, they have been extensively studied [96][97][98].…”
Section: Loading Ldh On Substratesmentioning
confidence: 99%
“…Absorption sites have also increased. Silica aerogel, N-doped carbon nanosheet, graphene, biochar, and other materials that can provide many absorption sites and stable attachment sites can be used as substrates [90][91][92][93][94][95]. Because carbon-based materials contain more functional groups and larger specific surface areas, they have been extensively studied [96][97][98].…”
Section: Loading Ldh On Substratesmentioning
confidence: 99%
“…For instance, the preparation of graphene requires concentrated H2SO4 and HNO3 for exfoliation. Recent studies have shown that biochars obtained from waste biomass, such as rice husk (Yu et al, 2018) and peanut shells (An et al, 2019), have great potential as cost-effective adsorbents for Ni and Pb remediation in soil and water. Biochar has a high capacity for adsorbing heavy metals because of its porous structure and inhomogeneous surface chemistry (Martin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This application has been attributed to the diversity and functionality of the interlayer region, in the LDH structure, that contains easily exchangeable intercalated anions and solvation molecules with hydrogen bonds. Moreover, the ability of LDH to remove soluble heavy metal ions was also explored [45]. However, regeneration of LDH and their agglomeration in solution restrict their application in water treatment [46], unless compounded with other materials in the form of functional composites that will minimize these shortcomings [47].…”
Section: Introductionmentioning
confidence: 99%